Off-Label Use of Bedaquiline in Children and Adolescents with Multidrug-Resistant Tuberculosis - Jay Achar; Cathy Hewison; Ana P. Cavalheiro; Alena Skrahina; Junia Cajazeiro; Parpieva Nargiza; Krzysztof Herboczek; Assliddin S. Rajabov; Jennifer Hughes; Gabriella Ferlazzo; James A. Seddon; Philipp du Cros (Emerging Infectious Diseases, 2017)
We describe 27 children and adolescents <18 years of age who received bedaquiline during treatment for multidrug-resistant tuberculosis. We report good treatment responses and no cessation attributable to adverse effects. Bedaquiline could be considered for use with this age group for multidrug-resistant tuberculosis when treatment options are limited.